The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1159/000485746
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Leptin Levels in New-Onset, Untreated Female Patients with Coronary Artery Disease and Positively Associated with Inflammatory Markers

Abstract: Background/Aims: Previous studies have suggested that leptin was associated with atherosclerosis and involved in inflammation. Gender differences between leptin and inflammatory markers have been evaluated less in untreated patients with stable coronary artery disease (CAD). Methods: In this study, a total of 394 consecutive Chinese patients who received coronary artery angiography were enrolled, including 243 patients with CAD and 151 non-CAD controls. The baseline clinical characteristics were collected and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Increased circulating leptin levels in patients with CAD have been associated with short-term occurrence of cardiac remodelling, impaired diastolic function, cardiac heart failure, cardiac death, acute coronary syndrome, and stroke [ 57 , 58 , 59 , 60 ]. In women with CAD, increased circulating leptin levels can predict cardiovascular death and non-fatal MI [ 61 , 62 ]. Regarding the endothelium, several studies have suggested that leptin contributes to endothelial dysfunction [ 63 , 64 , 65 ].…”
Section: Role Of Some Adipokines In Inflammatory Processes Associamentioning
confidence: 99%
“…Increased circulating leptin levels in patients with CAD have been associated with short-term occurrence of cardiac remodelling, impaired diastolic function, cardiac heart failure, cardiac death, acute coronary syndrome, and stroke [ 57 , 58 , 59 , 60 ]. In women with CAD, increased circulating leptin levels can predict cardiovascular death and non-fatal MI [ 61 , 62 ]. Regarding the endothelium, several studies have suggested that leptin contributes to endothelial dysfunction [ 63 , 64 , 65 ].…”
Section: Role Of Some Adipokines In Inflammatory Processes Associamentioning
confidence: 99%